Influence of governance indicators on illicit financial outflow from developing countries - Anselm Komla Abotsi (Contemporary Economics, 2018)
Economic growth has traditionally been attributed to the accumulation of human and physical capital and the increased productivity arising from technological innovation. The quest to attract physical capital led to the design and implementation of policies and the building of institutions by governments of developing countries to create a congenial investment environment to attract foreign investors. The multinational corporations operating in these developing countries take advantage of these policies to profit from these countries in terms of capital through both legal and fraudulent activities. For governments and stakeholders to be able to fight this menace of illicit financial outflow, there is a need for a comprehensive scrutiny of the quality of governance indicators that enhance the activities of these multinational companies. Therefore, this study seeks to explore the influence of cross-country indicators of governance on the illicit financial flow from developing countries. This study is based on secondary data (panel) derived from the Global Financial Integrity, World Development Indicators and Worldwide Governance Indicators. The total number of developing countries included in the analysis is 139, and 1562 observations are included. Using the multilevel estimation approach, the study finds that regulatory quality has a negative and significant influence on the illicit financial flow, while government effectiveness, corruption and FDI net inflows have a significant positive effect. This finding calls for developing countries to design and implement sound policies, build effective and accountable institutions, control corruption and enhance regulatory quality to control this issue.
Keywords: F18; F23; F20; F30; 330; illicit financial outflow; foreign direct investment; government effectiveness; corruption; regulatory quality